What Do People Desire in Others? A Sociofunctional Perspective on the Importance of Different Valued Characteristics - COTTRELL, Catherine A. (Institutional Knowledge at Singapore Management University, 2007)
Humans, as discriminately social creatures, make frequent judgments about others' suitability for interdependent social relations. Which characteristics of others guide these judgments and, thus, shape patterns of human affiliation? Extant research is only minimally useful for answering this question. On the basis of a sociofunctional analysis of human sociality, the authors hypothesized that people highly value trustworthiness and (to a lesser extent) cooperativeness in others with whom they may be interdependent, regardless of the specific tasks, goals, or functions of the group or relationship, but value other favorable characteristics (e.g., intelligence) differentially across such tasks, goals, or functions. Participants in 3 studies considered various characteristics for ideal members of interdependent groups (e.g., work teams, athletic teams) and relationships (e.g., family members, employees). Across different measures of trait importance and different groups and relationships, trustworthiness was considered extremely important for all interdependent others; the evidence for the enhanced importance of cooperativeness across different interdependence contexts was more equivocal. In contrast, people valued other characteristics primarily as they were relevant to the specific nature of the interdependent group or relationship. These empirical investigations illuminate the essence of human sociality with its foundation of trust and highlight the usefulness of a theoretically derived framework of valued characteristics.